Regional Variations in Health Disparities : A Cross-Regional Comparison of Self-Rated Health Determinants in Reform-era China - Kwon, Soyoung (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2016)
It is well documented that higher socioeconomic status is associated with favorable health status. Given regional variations in the pace and consequence of economic reform in China, this relationship may differ cross-regionally. Building upon the theoretical notion about distinct stratification system under state-socialism versus market economy, as well as the fundamental causes of health disparities, this study compares the association of education and cadre status with self-rated health across geographical regions (e.g., provinces) in reform-era China. Analyses of data pooled from the 1991-2000 China Health and Nutrition Survey reveal that the association between education and self-rated health is stronger in a more marketized region. Health benefits associated with a cadre status tend to decline in a more marketized region, which however fails to reach a statistical significance. The findings highlight the role regional contexts play in shaping health disparities in reform-era China.